An evaluation of fungal bioassay procedures for assessment of soil phosphate status : thesis presented at Massey University College of Manawatu in part fulfilment of the requirements for the degree of Master of Agricultural Science - Mantjika, N. M. D. (Massey University, 1963)
Microbiological assays, especially with A. niger, have been used rather widely to assess phosphate status of soils. The merits as well as shortcomings of these procedures have been discussed in the literature by various investigators. The speed, cheapness, and simplicity with which microbiological assays may be carried out have been used as arguments in favour of their use. It was this type of argument, considered in relation to the fact that good correlations have been reported by a number of workers between results obtained by A. niger and by field tests, which suggested to the writer that micro biological assay might have special merit in those developing countries where a rapid assessment of soil potential is required in the interests of food production but where limited finance is available for full-scale soil investigations. The work reported here was undertaken to investigate further the value of the A. niger procedure as a means of evaluating soil phosphate status and to examine the possibility that other fungi including some not previously employed for this purpose might be even more suitable. The present investigation was confined to a range of New Zealand soils. As field response data were not available for these soils a pot experiment incorporating a number of crops was conducted to provide plant growth data with which the results of microbiological assay could be correlated. [From Introduction]
Keywords: Soil physical chemistry; Biological assay